Flick the cancer stem cells' switch to turn cancer off - Christophe Ginestier; Daniel Birnbaum; Emmanuelle Charafe-Jauffret (Molecular & Cellular Oncology, 2017)
Tumors are organized in a cellular hierarchy with a population of cancer stem cell (CSC) driving cancer progression and resistance to treatment. Recently, we identified miR-600 as a bimodal switcher that balances breast CSC-fate from a self-renewing to a differentiation state, with a direct impact on tumor progression.